Stealth Alliance in South Asia: China-Pakistan Collaboration Reshaping Air Power and Regional Security (Journal of Social Sciences Review, 2025)
The growing military partnership between China and Pakistan is bringing a major shift to air-power in South Asia. This study investigates how the arrival of J-35A fighter jets from China to Pakistan is changing the balance of power in the region, mainly compared to India’s air forces. With stealth technology, access to real-time information from space and new rockets, the Beijing and Islamabad countries protect their economic projects and counter India in the air. With qualitative content analysis of military statements, other geopolitical materials and expert opinions, this paper studies the impact of the alliance on operations, the economy and politics. According to the results, the stealth partnership goes further than only transferring weapons and represents a real strategy with consequences for regional security. Suggestions call on nearby countries to reconsider how they protect themselves and communicate more to guide the developing state of political power.